(untitled) (African Journal of Biomedical Research, 2019)
Neuropsychiatric symptoms like cognitive impairment and anxiety are prominent in the perimenopausal period and have been related to increased oxidative stress. Study evaluated effect of L-arginine on these neuropsychiatric symptoms and oxidative stress parameters. Immature female Sprague-Dawley rats were divided into 3 groups; Premenopausal injected with Corn-oil (2.5μl/g) for 15 days; VCD perimenopausal, injected with 4-vinylcyclohexene diepoxide (160mg/kg) diluted in Corn-oil for 15 days; and AGING perimenopausal group. Fourteen weeks after VCD/corn-oil administrations, and 180 days in AGING perimenopausal group, rats were further divided into 2 sub-groups that received L-Arginine (100mg/kg) and distilled water for 30 days. Thereafter, neurobehavioural assessments were carried out in animals at diestrus using Y-maze and elevated plus maze. Animals were humanely sacrificed, hippocampus and frontal lobe were isolated from the brain and homogenized for measurement of oxidative stress parameters. Percentage correct alternation was significantly higher (P< 0.05) in premenopausal compared to VCD and AGING perimenopausal groups. It was significantly lower (P < 0.05) in AGING perimenopausal group administered distilled water compared to AGING perimenopausal group administered L-Arginine with no change in other groups. Close Vs Open arm ratio was significantly lower (P < 0.05) in premenopausal compared to VCD and AGING perimenopausal groups. Similarly, L-Arginine significantly reduced (P < 0.05) Close Vs Open arm ratio in AGING PRM group while it significantly improved (P < 0.05) oxidative stress parameters in all groups. L-arginine improved cognition and anxiety in AGING perimenopausal with no change in premenopausal and VCD perimenopausal rats.